Development of ‘Leave No One Behind’ indicators on Sustainable Development Goals and targets for ClimBeR project countries - Chakrabarti, P. G. D.; Amarnath, Giriraj (International Water Management Institute, 2023)
CGIAR Initiative on Climate Resilience (ClimBeR) focuses on seven representative, low and middle income countries in Africa, Asia and Latin America naming Kenya Morocco, Senegal, Zambia, Philippines, Sri Lanka and Guatemala. One of the work packages of the project involves development of LNOB indicators for the project countries across the entire spectrum of Sustainable Development Goals (SDG). LNOB or ‘Leave No One behind’ is the overarching philosophy of 2030 Agenda for Sustainable Development adopted by the United Nations, cutting across all the SDGs and its targets. The UN system has developed through consultative process a set of indicators for measuring progress of these goals and targets, but no separate indicators have been developed on LNOB. This paper has ventured into the tasks of developing LNOB indicators on SDGs, examine the requirements of disaggregated data for measuring progress on these indicators, explore the availability of such data within the UN system and the national statistical systems of the ClimBer project countries, and recommend a set of LNOB indicators that can be adopted for the project. The paper is structured in seven sections. Section one introduces the philosophy of Leave No One Behind (LNOB) and section two unpacks the philosophy into its three main components – equality, non-discrimination and empowerment. Section three provides an overview of 17 Sustainable Goals, and its 169 targets, as included in 2030 Agenda for Sustainable Development. A set of 231 unique indicators for measuring progress in the implementation of these goals and targets, and the tier classification of the indicators is also presented in this section. Section four identifies 100 unique indicators that are relevant for measuring progress on LNOB, and examines the disaggregation of data required on each of these indicators. It is found that 97 out of 100 LNOB indicators require disaggregation on more than 1 out 10 parameters identified for disaggregation, such as sex, age, income, education, occupation, disability, location, ethnicity or indigenous status and status of citizenship. Section five examines the availability of disaggregated data on LNOB indicators within the UN system for countries in general and for ClimBer project countries in particular. It further examines the availability of disaggregated data within the statistical systems of the seven ClimBer project countries. It is found conclusively that the required datasets are not available in the project countries on the LNOB indicators and it is not possible to develop or construct such data within the time span of the project.Section six suggests that even though LNOB indicators based on 17 SDGs and their targets cannot be adopted for the project, it is possible to develop project based LNOB indicators aligned with the SDGs. A set of 12 such ClimBer project based indicators are developed on which disaggregated data can be generated within the project. Section seven sums up the main recommendations of the study for the consideration of the ClimBer project authorities.